Stability of Mina v2 for Robot-Assisted Balance and Locomotion - Mummolo, Carlotta; Peng, William Z.; Agarwal, Shlok; Griffin, Robert; Neuhaus, Peter D.; Kim, Joo H. (Frontiers in Neurorobotics, 2018)
The assessment of the risk of falling during robot-assisted locomotion is critical for gait control and operator safety, but has not yet been addressed through a systematic and quantitative approach. In this study, the balance stability of Mina v2, a recently developed powered lower-limb robotic exoskeleton, is evaluated using an algorithmic framework based on center of mass (COM)- and joint-space dynamics. The equivalent mechanical model of the combined human-exoskeleton system in the sagittal plane is established and used for balance stability analysis. The properties of the Linear Linkage Actuator, which is custom-designed for Mina v2, are analyzed to obtain mathematical models of torque-velocity limits, and are implemented as constraint functions in the optimization formulation. For given feet configurations of the robotic exoskeleton during flat ground walking, the algorithm evaluates the maximum allowable COM velocity perturbations along the fore-aft directions at each COM position of the system. The resulting velocity extrema form the contact-specific balance stability boundaries (BSBs) of the combined system in the COM state space, which represent the thresholds between balanced and unbalanced states for given contact configurations. The BSBs are obtained for the operation of Mina v2 without crutches, thus quantifying Mina v2’s capability of maintaining balance through the support of the leg(s). Stability boundaries in single and double leg supports are used to analyze the robot’s stability performance during flat ground walking experiments, and provide design and control implications for future development of crutch-less robotic exoskeletons.